2020
DOI: 10.3126/jnprossoc.v3i1.34758
|View full text |Cite
|
Sign up to set email alerts
|

Infection Control Measures among Dental Professionals, Interns, and Students in Prosthodontic Department

Abstract: Introduction: Dental professionals frequently encounter infectious agents. Those not practicing proper infection control measures are at serious risk of infections. This study was conducted to assess knowledge, attitude, practice, and satisfaction of dental professionals regarding infection control guidelines to be followed in Prosthodontics. Materials and Methods: This cross-sectional descriptive study was conducted from August to October 2020 in department of Prosthodontics, Kathmandu Medical College a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
0
1
Order By: Relevance
“…Another survey conducted among dentists, interns and students of prosthodontics department of Kathmandu Medical College, Nepal reported that around 50% -65% participants disinfect rubber bowls, mixing spatulas, face bows and shade guides. The same research reported that around 60% participants autoclave, facebow fork, and fox occlusal plane 24 .On the other hand, results of our study reported that only around 35-40% participa-nts disinfect rubber bowls, mixing spatulas, face bows and shade guides. In comparison, adherence to sterilization of various instruments used during treatment was much better by our study participants.…”
Section: Discussioncontrasting
confidence: 44%
“…Another survey conducted among dentists, interns and students of prosthodontics department of Kathmandu Medical College, Nepal reported that around 50% -65% participants disinfect rubber bowls, mixing spatulas, face bows and shade guides. The same research reported that around 60% participants autoclave, facebow fork, and fox occlusal plane 24 .On the other hand, results of our study reported that only around 35-40% participa-nts disinfect rubber bowls, mixing spatulas, face bows and shade guides. In comparison, adherence to sterilization of various instruments used during treatment was much better by our study participants.…”
Section: Discussioncontrasting
confidence: 44%